2015
DOI: 10.5303/jkas.2015.48.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Large SDSS Quasar Groups and Their Statistical Significance

Abstract: Abstract:We use a volume-limited sample of quasars in the Sloan Digital Sky Survey (SDSS) DR7 quasar catalog to identify quasar groups and address their statistical significance. This quasar sample has a uniform selection function on the sky and nearly a maximum possible contiguous volume that can be drawn from the DR7 catalog. Quasar groups are identified by using the Friend-of-Friend algorithm with a set of fixed comoving linking lengths. We find that the richness distribution of the richest 100 quasar group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Nadathur (2013), Einasto et al (2014), and Park et al (2015) pointed out that the cosmological interpretation by Clowes et al (2013) of large quasar groups, which questions the validity of the cosmological assumption of homogeneity and isotropy, is misleading. They stressed the importance of a statistically precise analysis in order to draw conclusions on cosmological implications from the observation of one or a few extreme objects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nadathur (2013), Einasto et al (2014), and Park et al (2015) pointed out that the cosmological interpretation by Clowes et al (2013) of large quasar groups, which questions the validity of the cosmological assumption of homogeneity and isotropy, is misleading. They stressed the importance of a statistically precise analysis in order to draw conclusions on cosmological implications from the observation of one or a few extreme objects.…”
Section: Introductionmentioning
confidence: 99%
“…Using these quasar survey data, Clowes et al (2013), Nadathur (2013), Einasto et al (2014), and Park et al (2015) found very large quasar groups and discussed the cosmological implications of the existence and properties of these extreme objects. Nadathur (2013), Einasto et al (2014), and Park et al (2015) pointed out that the cosmological interpretation by Clowes et al (2013) of large quasar groups, which questions the validity of the cosmological assumption of homogeneity and isotropy, is misleading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still larger structures based on the SDSS have been reported; in particular, the Sloan Great Wall 420 Mpc long (Gott et al 2005), and the largest filamentary structure extending above 1 Gpc found in the DR7QSO catalogue (Clowes et al 2013). However, statistical significance of the latter one was questioned by Park et al (2015) on the grounds that group finding algorithm used by Clowes et al (2013) was not sufficiently restrictive and structures formed by chance were recognized as physical quasar group.…”
Section: Introductionmentioning
confidence: 95%
“…A question of identifying structures is of statistical nature and has a long history. It was recently discussed by Park et al (2015). Here we examine statistics of large voids found in the SDSS DR7 quasar catalogue.…”
Section: Introductionmentioning
confidence: 99%